Analysis of e-worksheet based on SDG-13 in climate change material - Nurul Fadilah; Anggi Tias Pratama; Agung Subiantoro (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
E-worksheets are needed to support learning of SDG-13 material on climate change material, but analysis related to this has not attracted much attention from researchers. The purpose of this study was to determine the needs of students related to digital-based teaching materials that they want to apply in the classroom in biology learning, especially on climate change material to show the phenomenon of global warming with the application of the Merdeka Curriculum. The use of digital-based media is still very suboptimal in utilization, especially in the material of climate change in biology subjects. This quantitative research was conducted using questionnaire techniques, namely giving questionnaires to X-grade students in two schools, namely SMAN in Yogyakarta and SMAN in South Sulawesi Regency, and descriptive techniques were used for analysis tools. The results of student respondents show that 100% want to use electronic worksheets as a learning medium on climate change material. The implication of this research is expected to increase the potential use of digital-based teaching materials and realize the 21st-century era that relies on technology.